Deregulation of Circular RNAs in Cancer From the Perspectives of Aberrant Biogenesis, Transport and Removal - Wu, Qiongqiong; Li, Peiyao; Wu, Minghua; Liu, Qiang (Frontiers in Genetics, 2019)
CircRNAs (circular RNAs) are a class of RNAs generated from circularization with multiple novel functions. Recent studies have revealed the aberrant expression and aberrant functions of circRNAs in various tumors; thus, circRNAs have been recognized as promising cancer biomarkers. However, the underlying mechanisms behind their aberrant expression and functions remain unclear. In this review, we discuss at length the cancer-specific deregulation of circRNAs and the potential underlying aberrant events in circRNA biogenesis, localization and removal in cancer cells.